THE MAPPING OF MOVEMENT VERBS FOUND IN THE GOOD EARTH - I Made Juliarta (LET: Linguistics, Literature and English Teaching Journal, 2020)
This study aimed at focussing the translation of movement verbs in The Good Earth written by Pearl S. Buck. The Natural Semantic Metalanguage (NSM) is applied in translation process. The novel The Good Earth was chosen as data source because it has two texts which have different language types. This study has the purpose to describe the application of translation procedures that is proposed by Vinay and Darlbener and it is applied to examine the mapping of Action Verbs by the NSM (Natural Semantic Metalanguage) theory. The analysis was shown as the mapping between Indonesian and English action verbs which was presented into the subtype of the verbs based on the classification. This study attempts to apply that theory in solving the problem of the different language.  Semantic mapping (SM) is a method in statistics for dimensionality reduction that can be used in a set of multidimensional vectors of features to extract a few new features that preserves the main data characteristics. Translation is very important in various areas which are used to translate from one language into another language. However, it is not all the references written in Indonesian as they are coming from different countries and use different languages.